Envelope Deglycosylation Enhances Antigenicity of HIV-1 gp41 Epitopes for Both Broad Neutralizing Antibodies and Their Unmutated Ancestor Antibodies - Ma, Ben-Jiang; Alam, S. Munir; Go, Eden P.; Lu, Xiaozhi; Desaire, Heather; Tomaras, Georgia D.; Bowman, Cindy; Sutherland, Laura L.; Scearce, Richard M.; Santra, Sampa; Letvin, Norman L.; Kepler, Thomas B.; et al. (PLoS pathogens, 2011)
The HIV-1 gp41 envelope (Env) membrane proximal external region (MPER) is an important vaccine target that in rare subjects can elicit neutralizing antibodies. One mechanism proposed for rarity of MPER neutralizing antibody generation is lack of reverted unmutated ancestor (putative naive B cell receptor) antibody reactivity with HIV-1 envelope. We have studied the effect of partial deglycosylation under non-denaturing (native) conditions on gp140 Env antigenicity for MPER neutralizing antibodies and their reverted unmutated ancestor antibodies. We found that native deglycosylation of clade B JRFL gp140 as well as group M consensus gp140 Env CON-S selectively increased the reactivity of Env with the broad neutralizing human mAbs, 2F5 and 4E10. Whereas fully glycosylated gp140 Env either did not bind (JRFL), or weakly bound (CON-S), 2F5 and 4E10 reverted unmutated ancestors, natively deglycosylated JRFL and CON-S gp140 Envs did bind well to these putative mimics of naive B cell receptors. These data predict that partially deglycoslated Env would bind better than fully glycosylated Env to gp41-specific naïve B cells with improved immunogenicity. In this regard, immunization of rhesus macaques demonstrated enhanced immunogenicity of the 2F5 MPER epitope on deglyosylated JRFL gp140 compared to glycosylated JRFL gp140. Thus, the lack of 2F5 and 4E10 reverted unmutated ancestor binding to gp140 Env may not always be due to lack of unmutated ancestor antibody reactivity with gp41 peptide epitopes, but rather, may be due to glycan interference of binding of unmutated ancestor antibodies of broad neutralizing mAb to Env gp41.